1985
DOI: 10.1002/1097-0142(19850915)56:6<1311::aid-cncr2820560615>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Aziridinylbenzoquinone in recurrent, progressive glioma of the central nervous system. A phase ii study by the illinois cancer council

Abstract: Aziridinylbenzoquinone (AZQ) was studied in a Phase II protocol for persons with glioma of the central nervous system (CNS) recurrent or progressive after surgery and radiotherapy. Patients received AZQ, 30 mg/m2 intravenously every 3 weeks if previously untreated or 27.5 mg/m2 if previously exposed to cytotoxic drugs. Partial response was defined as a reduction of at least 50% reduction in the product of the two longest perpendicular diameters of the indicator lesion persisting for a minimum of 28 days. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…They were treated with various dosage schedules, including a five consecutive day regimen as reported herein, a three or four weekly schedule, a daily times two dose schedule, and a day one and eight schedule. Neither the total dose of AZQ administered per course nor the dosage regimen appears to have an impact on the response rate, although there are no comparative trials [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were treated with various dosage schedules, including a five consecutive day regimen as reported herein, a three or four weekly schedule, a daily times two dose schedule, and a day one and eight schedule. Neither the total dose of AZQ administered per course nor the dosage regimen appears to have an impact on the response rate, although there are no comparative trials [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The responses by diagnosis are listed in Table 2. Prolonged stable disease while on therapy with AZQ was seen in four patients with ependymoma (6,8,12, and 18 months), two patients with PNET (10+ and 27+ months), and one patient with medulloblastoma (8 months). A 3 3/4 year old patient with an ependymoma of the fourth ventricle was placed on AZQ when he developed intracranial metastases in the right frontal horn and the inferior aspect of the third ventricle.…”
Section: Therapeutic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In the absence of therapy, OS is limited to 30-35 weeks. [10][11][12][13] The poor outcome for GBM patients is largely due to the molecular and cellular heterogeneity of the cancer, which equips the tumor with multiple strategies for adapting to and overcoming the effects of therapy.…”
Section: Malignant Gliomamentioning
confidence: 99%
“…A number of clinical trials showed response rates of approximately 20% in patients with high-grade or progressive gliomas treated with diaziquone (148,149) and approximately 25% in patients with astrocytic neoplasms treated with diaziquone and either BCNU or procarbazine (150). However, phase III trials comparing diaziquone to the nitrosoureas, BCNU or PCNU, found that diaziquone was not significantly better than BCNU (151) and was less effective than PCNU (152) in patients with brain tumors.…”
Section: Clinical Studiesmentioning
confidence: 99%